2016
DOI: 10.1097/coc.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Pathologic Risk Factors May Reduce the Rate of Multimodality Treatment of Early Cervical Cancer

Abstract: This study suggests that in patients with early cervical cancer, clinicopathologic evaluation of tumor size and lymph-vascular space invasion should be undertaken before performing radical hysterectomy. This approach can serve to tailor treatment, reducing the rate of employing both radical hysterectomy and chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…Recent literature, especially with the advent of more and more fertility sparing surgery suggests tumor size more than 2 cm is a risk factor. [82][83][84][85][86][87][88][89][90][91] . In a recent study, Gemer et al 91…”
Section: It Was Incorporated In the Figo Staging System As Stage Ib2mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature, especially with the advent of more and more fertility sparing surgery suggests tumor size more than 2 cm is a risk factor. [82][83][84][85][86][87][88][89][90][91] . In a recent study, Gemer et al 91…”
Section: It Was Incorporated In the Figo Staging System As Stage Ib2mentioning
confidence: 99%
“…Since 2009 it was incorporated in the FIGO staging system as Stage IB2 and now in the 2018 staging revision as Stage IB3. Recent literature, especially with the advent of more and more fertility sparing surgery suggests tumor size more than 2 cm is a risk factor …”
Section: Management Of Cervical Cancermentioning
confidence: 99%
“…This inconsistence could be explained by the disparity in the nomenclature of lymph node groups; the lymph nodes caudal to the deep circumflex iliac vessels were included in the external iliac in our study. Among the known risk factors of LNM in patients with early stage cervical cancer, tumour size and LVSI are assessable before surgery through imaging and histological evaluation of specimens of conisation, loop electrical excision procedure, and cervical biopsy, respectively [26,27]. Interestingly, in the present study, LVSI was identified as an independently predictive for metastasis in all three lower groups of pelvic lymph nodes but not in common iliac LNM; on the contrary, tumour size was a robust predictor for common iliac LNM but not significantly associated with lower pelvic node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Patients with pathological risk factors (e.g., LNM, tumor-positive surgical margins, depth of invasion, vascular thrombosis, interstitial infiltration depth, tumor stage, and tumor differentiation) have a higher frequency of recurrence when compared to patients without those factors. [7] At the same time, especially recent studies have found that the size of tumors over 2 cm may also be a poor prognostic factor, [812] which has a certain correlation with the depth of invasion of tumors. Hence, it is vital to analyze the influence of different risk factors on the prognosis of patients with early-stage cervical cancer, which also decides how to plan adjuvant treatment after surgery.…”
Section: Introductionmentioning
confidence: 99%